An interactive online dashboard for tracking COVID-19 in U.S. counties, cities, and states in real time. (17th June 2020) - Wissel, Benjamin D; Van Camp, P J; Kouril, Michal; Weis, Chad; Glauser, Tracy A; White, Peter S; Kohane, Isaac S; Dexheimer, Judith W
Abstract: Objective: The study sought to create an online resource that informs the public of coronavirus disease 2019 (COVID-19) outbreaks in their area. Materials and Methods: This R Shiny application aggregates data from multiple resources that track COVID-19 and visualizes them through an interactive, online dashboard. Results: The Web resource, called the COVID-19 Watcher, can be accessed online (https://covid19watcher.research.cchmc.org/ ). It displays COVID-19 data from every county and 188 metropolitan areas in the United States. Features include rankings of the worst-affected areas and auto-generating plots that depict temporal changes in testing capacity, cases, and deaths. Discussion: The Centers for Disease Control and Prevention does not publish COVID-19 data for local municipalities, so it is critical that academic resources fill this void so the public can stay informed. The data used have limitations and likely underestimate the scale of the outbreak. Conclusions: The COVID-19 Watcher can provide the public with real-time updates of outbreaks in their area.